Asymmetrical Hearing Loss in Cases of Industrial Noise Exposure: A Systematic Review of the Literature. Issue 8 (September 2016) - Masterson, Liam; Howard, James; Liu, Zi Wei; Phillips, John
Abstract : Objective: Asymmetrical hearing thresholds are common in people claiming compensation for noise-induced hearing loss (NIHL). When present and otherwise unexplained, there is some controversy as to whether such asymmetry can be attributed to occupational noise exposure. In this review, our main objectives were to collate the overall prevalence of this finding in subjects with NIHL, and further, to provide a balanced argument regarding causality. Data Sources: MEDLINE, CINAHL, EMBASE, Cochrane, Google Scholar. No date or language restrictions. Study Selection and Data Extraction: A systematic review of the literature was performed and data on noise exposure, pure tone audiometry, and lateralized hearing outcomes were reviewed. Newcastle-Ottawa (N-O) criteria were employed to assess quality of studies where applicable. Data Synthesis: N/A Conclusion: Six studies met the inclusion criteria giving a total of 4, 735 individual cases with NIHL. Asymmetrical hearing loss accounted for between 2.4% and 22.6% of NIHL cases (L-R difference >15 dB for any frequency 0.5–8 kHz). However, the overwhelming majority of subjects in this review have symmetrical hearing loss when adjusted for other significant variables, e.g., age, sex, and binaural hearing deterioration. Subjects considered for noise exposure remuneration were men (94.3% SE ± 2.7), aged 52.9 years (inter-quartile range, 46.1–58.4), and from a broad range of industrial backgrounds. Future research will be needed to establish the influence of other factors such as smoking status, exposure to chemical agents, specific drugs, or genetic predisposition.